1976
DOI: 10.1152/physrev.1976.56.4.652
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclic nucleotides in cell growth and differentiation

Abstract: A simple model is depicted below that suggests some unifying principals in the action of cyclic nucleotides in the GO-to-G+ interconversion, differentiation, and transformation (see article). The letters with G+ subscripts (AG+ through EG+) represent cell states at different increasing levels of "determination" (see sect. vE). Cells in each of these states are continuously reproducing themselves through cell division (i.e., they are in G+). As an alternative to cell reporduction, cells at each level may move t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
93
0
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(104 citation statements)
references
References 0 publications
9
93
0
2
Order By: Relevance
“…EXPERIMENTAL EVIDENCE suggests that cyclic adenosine 3',5'-monophosphate (cAMP) and cyclic guanosine 3',5'-monophosphate (cGMP) play opposite roles in the control of cell growth and differentiation (Goldberg et al, 1975;Pastan et al, 1975;Watson, 1975;Friedman, 1976). In vitro, exogenous cGMP stimulates the proliferation of fibroblasts and lymphoid cells Whitfield et al, 1971;Diamantstein & Ulmer, 1975;Watson, 1975) whereas cAMP, or agents which increase its intracellular concentration, inhibit cell growth (Ryan & Heidrick, 1968;Yang & Vas, 1971;Pardee, 1974) and induce in malignant cells a normalappearing morphological or biochemical differentiation (Hsie & Puck, 1971;Johnson et al, 1971;Prasad et al, 1975).…”
mentioning
confidence: 99%
“…EXPERIMENTAL EVIDENCE suggests that cyclic adenosine 3',5'-monophosphate (cAMP) and cyclic guanosine 3',5'-monophosphate (cGMP) play opposite roles in the control of cell growth and differentiation (Goldberg et al, 1975;Pastan et al, 1975;Watson, 1975;Friedman, 1976). In vitro, exogenous cGMP stimulates the proliferation of fibroblasts and lymphoid cells Whitfield et al, 1971;Diamantstein & Ulmer, 1975;Watson, 1975) whereas cAMP, or agents which increase its intracellular concentration, inhibit cell growth (Ryan & Heidrick, 1968;Yang & Vas, 1971;Pardee, 1974) and induce in malignant cells a normalappearing morphological or biochemical differentiation (Hsie & Puck, 1971;Johnson et al, 1971;Prasad et al, 1975).…”
mentioning
confidence: 99%
“…By the 1970s, however, cAMP was implicated as a regulator of cell growth (25)(26)(27), and several investigators reported that the elevation of cAMP levels induced proliferation arrest or cell death in susceptible normal or malignant lymphoid populations (28)(29)(30)(31)(32)(33). The cAMP signaling pathway has emerged as a key regulator of hematopoietic cell proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results verify that guanylate cyclase was the effector of YC-1, and the anti-proliferative effect of YC-l was mediated by cGMP. cGMP has been reported to inhibit the proliferation of VSMCs [32,37], but the molecular mechanisms of this anti-proliferative action remain to be clarified. Inhibition of proliferation of cGMP-elevating agents (e.g.…”
Section: Concnmentioning
confidence: 99%